Mathematical modeling and optimal control of multi-strain COVID-19 spread in discrete time - Elqaddaoui, Ahmed; El Bhih, Amine; Laarabi, Hassan; Abta, Abdelhadi; Rachik, Mostafa (Frontiers in Applied Mathematics and Statistics, 2024)
This research article presents a mathematical model that tracks and monitors the spread of COVID-19 strains in a discrete time frame. The study incorporates two control strategies to reduce the transmission of these strains: vaccination and providing appropriate treatment and medication for each strain separately. Optimal controls were established using Pontryagin's maximum principle in discrete time, and the optimality system was solved using an iterative method. To validate the effectiveness of the theoretical findings, numerical simulations were conducted to demonstrate the impact of the implemented strategies in limiting the spread of COVID-19 mutant strains.